Lactancia materna y alimentación complementaria en niños de dos años del área de influencia del Subcentro de Salud El Aguador de la ciudad de Machala. - Aguilar Gavilanes, Sandy S. (2011)
During children’s growth there’s period of greater vulnerability that extends from birth until about age 2 this is why a quality feeding is recommended during this period, emphasizing breast-feeding as ideal up to the sixth month, then an appropriate and diverse introduction of different foods is recommend.